133. Dose plan investigation comparing Free Breathing (FB) and Deep Inspiration Breath Hold (DIBH): Error assessment in gating window is possible. (December 2018) - Ferrari, P.; Maffei, M.; Bouselman, S.; Hofer, S.; Haller, M.
Abstract: Purpose: Since 90's Darby et all show as breast cancer radiotherapy appreciably increased mortality from heart disease and lung cancer 10–20 years afterwards with. Our aim is to investigate introduction of DIBH in breast cancer radiotherapy, comparing dose distribution with FB and to assess margin of error. Methods: FB and DIBH plans were performed using RayStation (RaySearch Laboratories) in 24 patients. DVH and dose statistics were compared, deformable registration performed to assess doses in DIBH and FB combined treatments. Perturbed dose in DIBH was computed to assess variability in the gating window (4 mm). Results: DIBH plan showed a significant (p < 0.005) reduction in the mean dose of Heart, Left Ventricle and Left Anterior Descending Artery (LAD) respectively 54%, 62% and 64% and perturbed dose calculation in DIBH determined a variability in the respective mean dose of 27%, 28% and 24% in the gating window range of 4 mm. Conclusions: DIBH is a robust method to reduce radiation dose to the heart, and consequently reduce the heart disease mortality rate ratio[1] . Our method warranty total assessment in the dose variability due to the gating window and in case of DIBH interruption, the dose computation in DIBH and FB combined treatment, with the total control of heart doses.